2010
DOI: 10.1001/jama.2010.449
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Sweetener Consumption and Dyslipidemia Among US Adults

Abstract: Context Dietary carbohydrates have been associated with dyslipidemia, a lipid profile known to increase cardiovascular disease risk. Added sugars (caloric sweeteners used as ingredients in processed or prepared foods) are an increasing and potentially modifiable component in the US diet. No known studies have examined the association between the consumption of added sugars and lipid measures. Objective To assess the association between consumption of added sugars and blood lipid levels in US adults. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
2
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(168 citation statements)
references
References 25 publications
9
152
2
5
Order By: Relevance
“…An interesting finding, shown in figure5, indicated a clear correlation between high consumption of sugar or sweeteners and a prevalence of cholesterol in men and women. This result appears to be an important finding from the health point of view (see also [11,12]). …”
Section: Correlation Analysissupporting
confidence: 54%
“…An interesting finding, shown in figure5, indicated a clear correlation between high consumption of sugar or sweeteners and a prevalence of cholesterol in men and women. This result appears to be an important finding from the health point of view (see also [11,12]). …”
Section: Correlation Analysissupporting
confidence: 54%
“…Following the worldwide trend revealing a considerable increase in overweight (OW) and OB prevalence during childhood in developed countries (6,7) , recent studies in Greek populations show very high rates of childhood OW and OB and aggravating dietary and lifestyle habits (8,9) . The potential link between excessive intake of free sugars, OB and other health outcomes, including diabetes and CVD risk factor alterations, has been pointed out as an important public health matter, not only in adults but in adolescents as well (10)(11)(12)(13) . Studies on the effects of sugar consumption on weight status or gain have shown mixed results.…”
mentioning
confidence: 99%
“…Evidence indicating the relationship between the consumption of added sugars and colorectal cancer has also been published [44][45][46]. Furthermore, the increase in plasma triglycerides and LDL cholesterol, and the decrease in High-Density Lipoprotein (HDL), is typical of dyslipidemia [47] and may be caused by excessive consumption of added sugars [48]. Individuals with higher intakes of added sugars had higher serum triglyceride, total cholesterol, and LDL levels than those with lower intake, according to a systematic review [49].…”
Section: Sugar Metabolism and Health Effectsmentioning
confidence: 99%